When Is the Right to Justice Undermined? Identifying and Applying International and Islamic Human Rights Law Standards for Domestic Judicial Processes: The Case of the Seven Bahá’í Leaders and Iran’s Revolutionary Courts - Ghahraman, Golriz (Religion and human rights, 2016)
Section one of this article is divided in two parts, defining a ‘competent tribunal established by law’, and secondly independence and impartiality, including both structural and substantive standards for assessment. The second section provides an assessment of the legitimacy of the process in terms of minimum standards of due process. This part consists of three sub-sections, addressing three aspects of the right to due process that most gravely risk political manipulation of trials. These are: the principle of legality; procedural transparency; and the right to be represented by competent defence counsel. Both these sections also apply the components identified to the general operation of Iran’s Revolutionary Courts. Finally, section three will analyse the conduct of Iran’s Revolutionary Courts in the particular trials of the seven Bahá’í leaders (known as the ‘Yaran’ or ‘friends’) in Iran in 2010.